(untitled) (Biological Sciences - PJSIR, 2000)
Concentration dependence of the adiabatic compressibility and velocity in aqueous solutions of various concentrations of glycols atmospheric pressure have been studied using the ultrasonic interferometric technique, the measurements have been performed a12 MHz, in the temperature range 25 to 40°C. The adiabatic compressibility has been evaluated from the collected data. The dependence of compressibility and sound velocity on the concentration at adiabatic conditions have been evaluated with average density at four different temperatures. The molecular interaction has also been evaluated from the data collected, using its excess value to determine their thermodynamic properties. It reveals that the change in velocity is maximum in one of the three glycol solutions and compressibility is minimum at a particular concentration.